Glycemic load, exercise, and monitoring blood glucose (GEM): A paradigm shift in the treatment of type 2 diabetes mellitus. (January 2016) - Cox, Daniel J.; Taylor, Ann G.; Singh, Harsimran; Moncrief, Matthew; Diamond, Anne; Yancy, William S.; Hegde, Shefali; McCall, Anthony L.
Abstract: Aims: This preliminary RCT investigated whether an integrated lifestyle modification program that focuses on reducing postprandial blood glucose through replacing high with low glycemic load foods and increasing routine physical activities guided by systematic self-monitoring of blood glucose (GEM) could improve metabolic control of adults with type 2 diabetes mellitus, without compromising other physiological parameters. Methods: Forty-seven adults (mean age 55.3 years) who were diagnosed with type 2 diabetes mellitus for less than 5 years (mean 2.1 years), had HbA1c ≥7% (mean 8.4%) and were not taking blood glucose lowering medications, were randomized to routine care or five 1-h instructional sessions of GEM. Assessments at baseline and 6 months included a physical exam, metabolic and lipid panels, and psychological questionnaires. Results: The GEM intervention led to significant improvements in HbA1c (decreasing from 8.4 to 7.4% [69–57 mmol/mol] compared with 8.3 to 8.3% [68–68 mmol/mol] for routine care; Interaction p < .01) and psychological functioning without compromising other physiological parameters. Conclusions: Consistent with a patient-centered approach, GEM appears to be an effective lifestyle modification option for adults recently diagnosed with type 2 diabetes mellitus.